Experimental Study of the reaction [Fórmula Matemática] MeV using the GASP array (2014)
Abstract. In this thesis an experimental study of the binary nuclear reaction [Formula Matematical] MeV using the Gasp and Prisma-Clara arrays at Legnaro National Laboratory (LNL), Legnaro, Italy is presented. The experiments populate a wealth of projectile-like and targetlike binary fragments, in a large neutron-rich region below the magic number Z = 50 and at the right side of the magic number N = 50, using multinucleon-transfer reactions. The data analysis is carried out by γ-ray spectroscopy. The experimental yields of the reaction in each one of the experiments, is presented. Results on the study of the yrast and near-yrast excited states of [Formula Matematical] are presented, along with a comparison of the predictions by shell model calculations.